The Vilnius School of Old Believers’ Icon Painting: Ivan Mikhailov and his Students - Поташенко, Григорий (Slavistica Vilnensis, 2018)
[full article, abstract in Russian; abstract in Lithuanian and English] Ivan Ipatievich Mikhailov (1893–1993) — an outstanding and fruitful Vilnius-based icon painter of the 20th century. New studies suggest that has made a significant contribution to the preservation and development of the Old Believers’ icon painting tradition in Lithuania, Belarus, Poland and Latvia in the 20th century. However, Mikhailov’s life and his creative heritage have only in recent years become the property of a wide range of researchers and experts in Russian iconography. In the 1970s and 1980s, Mikhailov was the founder of the Vilnius school of icon painting. Today, his students continue to work successfully in Lithuania, Latvia and Belarus. The purpose of this article is to consider the establishment, operation and teaching methods of the Vilnius school of icon painting that was headed by Ivan Mikhailov. One of the main sources of new and additional information about the facts, circumstances and features of the iconography of training were the stories of his daughter Zoya Mikhailova, an interview with four of his students and other people who knew the icon painter.